Risks associated with obesity in pregnancy, for the mother and baby: a systematic review of reviews. Issue 8 (28th May 2015) - Marchi, J.; Berg, M.; Dencker, A.; Olander, E. K.; Begley, C.
Summary Maternal obesity is linked with adverse outcomes for mothers and babies. To get an overview of risks related to obesity in pregnant women, a systematic review of reviews was conducted. For inclusion, reviews had to compare pregnant women of healthy weight with women with obesity, and measure a health outcome for mother and/or baby. Authors conducted full‐text screening, quality assurance using the AMSTAR tool and data extraction steps in pairs. Narrative analysis of the 22 reviews included show gestational diabetes, pre‐eclampsia, gestational hypertension, depression, instrumental and caesarean birth, and surgical site infection to be more likely to occur in pregnant women with obesity compared with women with a healthy weight. Maternal obesity is also linked to greater risk of preterm birth, large‐for‐gestational‐age babies, foetal defects, congenital anomalies and perinatal death. Furthermore, breastfeeding initiation rates are lower and there is greater risk of early breastfeeding cessation in women with obesity compared with healthy weight women. These adverse outcomes may result in longer duration of hospital stay, with concomitant resource implications. It is crucial to reduce the burden of adverse maternal and foetal/child outcomes caused by maternal obesity. Women with obesity need support to lose weight before they conceive, and to minimize their weight gain in pregnancy.